A corrosion failure analysis of heat exchanger tubes operating in petrochemical refinery. (January 2021) - Rezaei, Milad; Mahidashti, Zeynab; Eftekhari, Sajad; Abdi, Ehsan
Graphical abstract: Highlights: Erosion-corrosion was the main cause of tube heat exchanger failure. Erosion was induced by suspended solid particles in crude methanol passing by the tube halls. Five methods were proposed for corrosion reduction of the tubes. Abstract: The aim of this study was to analyze corrosion failure of heat exchanger tubes used in petrochemical refinery. Thermodynamic and kinetics analysis showed that the major chemical substance playing role in electrochemical corrosion of the tubes is solute CO2 present in crude methanol passing by the tubes. However, polarization tests revealed that corrosion caused by CO2 is not so significant to produce cavities observed on the outer surface of the tube. By further investigation of the morphology and previous processes in producing crude methanol, it was revealed that crude methanol contains significant amount of suspended solid particles with relatively high hardness, which were detached from the catalysts of the previous phases. Therefore, besides the electrochemical corrosion, the main mechanism of tubes corrosion was attributed to the erosion-corrosion. According to the corrosion cause, appropriate methods were proposed for corrosion prevention or corrosion reduction of the tubes.